Dynamics of cutting structural steels with end-milling cutters - A. N. Gavrilin; G. I. Korovin; P. S. Rozhkov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2009)
The article is devoted to optimization of structural steel milling modes when using special vibration-proof tool of the original construction.